Transverse deformation effect on sensitivity of strain-sensing patch antenna. (February 2020) - Wan, Chunfeng; Xie, Liyu; Xu, Kangqian; Xue, Songtao; Jiang, Can; Wan, Guochun; Ding, Tao
The strain sensor based on microwave patch antenna is proposed to monitor structural strain in structural health monitoring. When patch antenna experiences deformation, the resonant frequency of patch antenna will shift. With these characteristics, the patch antenna can operate as both the strain-sensing element and communication component. This article chooses an RT-5880 rectangular patch antenna for strain measurement, focusing on its sensing performance. For distinguishing the influence of deformation in the antenna's length direction and width direction, the numerical simulation is implemented, and then two kinds of laboratory experiments are conducted. The first approach is to paste antennas in longitudinal and transverse ways and solve the equation set. The other approach is to design another patch antenna with narrow width and compare the test results with the wide one. All results show that the influence of deformation in wide direction on sensitivity can be neglected, and the resonant frequency shift has a good linear relationship with the strain of antenna in length direction.